Lifestyle Influences on Body Shape Index and Oral Health in Patients Visiting Public Healthcare Facilities in Chennai- A Cross-sectional study - Balamurugan, Dhanus; Fathima, Lubna; Sujitha; Rajmohan , M; Sindhu , R; Dhamodhar, Dinesh; Nehru, Indira; Prabu , D (International Journal of Scientific Research in Biological Sciences, 2025)
Background: Asides from being an epidemic in and of itself, obesity is linked to a number of serious illnesses, such as diabetes, hypertension, cancer, and cardiovascular diseases, including dental problems. Aim: The study aims to evaluate the impact of sedentary lifestyles in terms of A Body Shape Index (ABSI) on oral conditions among general patients attending Primary Health Centres (PHC) in Chennai, India. Materials and Method: A cross-sectional descriptive study was carried out among 224 outpatients who visited PHCs from March to September 2024. Socio-demographic data was collected using self-administered questionnaires. A thorough clinical examination was carried out based on Oral Health Surveys Basic Methods (WHO, 2005) for the presence or absence of conditions like dental caries, gingivitis, and edentulism. Descriptive statistics and chi-square test to find the association between ABSI and oral hygiene. Kruskal Wallis test was performed to compare the risk groups of NCDs based on Body Shape Index with DMFT and OHI-S scores were carried out using SPSS 27.0 version. Results: A total of 224 participants; most patients visiting PHC were females (66.1%). The mean scores of Decayed teeth (DT), Missing teeth (MT), Filled teeth (FT), and DMFT scores of the population were 2.02±1.01, 0.23±1.37, 0.19±1.24 and 3.24±1.67 respectively. There is an association between the consumption of unhealthy diets and poor oral hygiene (p < 0.004). Conclusion: Results show a substantial association between poor dental health and unhealthy eating. It is high time that the government reforms its public policies related to unhealthy food consumption.